2014
DOI: 10.1134/s0006297914100113
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and therapeutic effects of SkQ1-containing Visomitin eye drops against light-induced retinal degeneration

Abstract: The human retina is constantly affected by light of varying intensity, this being especially true for photoreceptor cells and retinal pigment epithelium. Traditionally, photoinduced damages of the retina are induced by visible light of high intensity in albino rats using the LIRD (light-induced retinal degeneration) model. This model allows study of pathological processes in the retina and the search for retinoprotectors preventing retinal photodamage. In addition, the etiology and mechanisms of retina damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The animal models of LIRD are generally acknowledged for AMD studies as they share many common features with the human disease (discussed in [3]). Consistently, we previously demonstrated that exposure of the eyes of experimental animals (rats and rabbits) to different doses of bright visible light leads to the development of retinal degenerative processes, including the apoptosis of photoreceptors and other retinal neurons, as well as vacuolization of RPE cells, their phagocytic activity, and migration into the neural retina, representing common hallmarks of AMD [3,14,15,43]. In the present study, we used a rabbit model of LIRD that was induced by intense short-term illumination (30,000 lx for 3 h) [3,15].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The animal models of LIRD are generally acknowledged for AMD studies as they share many common features with the human disease (discussed in [3]). Consistently, we previously demonstrated that exposure of the eyes of experimental animals (rats and rabbits) to different doses of bright visible light leads to the development of retinal degenerative processes, including the apoptosis of photoreceptors and other retinal neurons, as well as vacuolization of RPE cells, their phagocytic activity, and migration into the neural retina, representing common hallmarks of AMD [3,14,15,43]. In the present study, we used a rabbit model of LIRD that was induced by intense short-term illumination (30,000 lx for 3 h) [3,15].…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, in previous LIRD studies, we have observed that focal signs of inflammation including disturbance in the blood-retinal barrier and inflammatory infiltration accompany the development of the degenerative changes in the retina. Indeed, retinal edema was found to already emerge at the early stages of LIRD, gradually expanding in the course of the disease and becoming complemented by granulocytic infiltration [14,43]. All of these signs were occasionally found in the model used in the current work, indicating that intraocular inflammation is a sustainable complication of LIRD.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…SkQ1 exhibits two-fold increased hydrogen peroxide inhibition potency compared with its derivative MitoQ1 61 . SkQ1 has been evaluated in vitro and in vivo and is currently approved as a droplet formulation (called Visomitin ® ) for eye diseases in Russia 108 .…”
Section: Mitochondria-targeting Ligand Conjugatesmentioning
confidence: 99%
“…Indeed, the essential features of human dry (non-neovascular) AMD can be reproduced in the models of light-induced retinal damage (LIRD) [15,16,17,18]. Our previous histological studies revealed that retinas of the animals exposed to various doses of light illumination exhibit such hallmarks of AMD as photoreceptor apoptosis, pigment epithelial cell migration into the neural retina, disturbance in blood-retinal barrier, and inflammatory infiltration [19,20]. The studies using these models may provide important information about general mechanisms of retinal photic damage underlying AMD and other degenerative retinal diseases.…”
Section: Introductionmentioning
confidence: 99%